Factors associated with dietary diversity score among individuals with type 2 diabetes mellitus - Tiew, Kee Fong; Chan, Yoke Mun; Lye, Munn Sann; Loke, Seng Cheong (International Center for Diarrhoeal Disease Research, 2014)
Studies on diet quality among individuals with type 2 diabetes mellitus (T2DM) are scarce. This crosssectional study aimed to assess the diet quality and to determine its associated factors among individuals with T2DM at the Medical Outpatients Department, Serdang Hospital, Selangor, Malaysia, from July 2010 to March 2011. Subjects were interviewed for sociodemographic data. Diabetes history was retrieved from the hospital’s e-database. Usual dietary intake was measured using a food frequency questionnaire, from which a dietary diversity score was obtained with two measures: Food Group Score and Serving Score were constructed based on the Malaysian Dietary Guidelines. Food Group Score was computed from the number of food groups consumed from five major food groups (grains, vegetables, fruits, meat, and dairy products) whereas Serving Score was computed from the number of servings consumed from the various food groups. Anthropometric measures, including weight, height, waist- and hip-circumference were examined. For data analyses, descriptive statistics, simple and multiple linear regression were conducted using IBM SPSS Statistics 20.0. A total of 113 subjects (50.4% female), with mean±SD age of 54.05±10.30 years and duration of diabetes of 11.25±9.05 years were studied. The mean Food Group Score and Serving Score were 4.12±0.79 and 12.75±3.50 respectively. Slightly more than one-third of the subjects achieved five food groups a day while less than 2% consumed a desirable number of servings from all food groups. Among the five food groups, dairy, and fruits were the least-frequently consumed foods. Lower education, lower personal income, working, non-insulin, overweight and obese subjects had significantly lower Food Group Score than their counterparts [F (6,106)=4.924, p<0.0001] whereas lower education, lower waist-to-hip ratio, overweight and obese subjects had significantly lower Serving Score than their counterparts [F (4,108)=7.520, p<0.0001]. There was a high proportion of individuals with T2DM, who failed to adhere to the national dietary guidelines. The importance of taking a well-balanced diet in accordance with the guidelines should be emphasized, especially among those with lower educational level through a simple and easy-to-understand approach.